Homo- and heterodimeric dyes for dye-sensitized solar cells: panchromatic light absorption and modulated open circuit potential - Sil, Manik Chandra; Sudhakar, Vediappan; Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ChemPlusChem, 2018)
The design of dyes for panchromatic light absorption has attracted much attention in the field of dye-sensitized solar cells (DSSCs). An approach to enhance panchromatic light absorption utilizes mixtures of complementary light-absorbing dyes as well as dyes with specific anchoring groups that facilitate interfacial charge transfer with TiO2. Dipole-dipole interactions between the dye molecules on the surface broaden the spectrum, which results in decreased DSSC device performance. However, controlled aggregation of dyes results in broadening the spectral profile along with enhanced photocurrent generation. To control the dye-dye interaction, dimeric dyes with different dipole lengths D-1-D-sq, D-sq-D(sq)were systematically designed and synthesized. The photophysical and electrochemical properties were evaluated and the E-HOMO and E-LUMO levels were determined; these energy levels determines the electron injection from E-LUMO of the dye to E-CB of TiO2 and regeneration of oxidized dye by the electrolyte, respectively. The absorption spectra of D-sq-D-sq, D-1-D-sq were broadened in solution compared to model dye D-sq; this indicates that the dye-dye interaction is prominent in solution. In D-1-D-sq excitation energy transfer between photoexcited D-1 and D-sq was explained by using Forster resonance energy transfer (FRET). The homodimeric dye showed a device performace of 2.8 % (V-oc 0.607, J(sc) 6.62 mA/cm(2), ff 69.3 %),whereas the heterodimeric dye D-1-D-sq showed a device performance of 3.9 % (V-oc 0.652 V, J(sc) 8.89 mA/cm(2), ff 68.8 %). The increased photocurrent for D-1-D(sq)is due to the panchromatic IPCE response compared to D-sq-D-sq. The increased V(oc)is due to the effective passivation of the TiO2 surface by the spirolinker, and the effective dipole moment that shifts the conduction band on TiO2. Hence, the open circuit potential, V-oc, for the devices prepared from D-sq, D-1-D-sq and D-sq-D(sq)were systematically modulated by controlling the intermolecular pi-pi and intramolecular dipole-dipole interactions of the dimeric dyes.

Highly efficient method of utilizing waste silica hazards - Singh, Anup Kumar; Sudhakar, Vediappan (Process Safety and Environmental Protection, 2021)
Silica gels are the significant commodity solid waste produced by organic laboratories and pharmaceutic industries. Although use of silica gels is continuously growing, the proper methods of re-utilizing silica waste are yet limited. Hence, it demands a non-traditional approach to transform these silica waste into some other useful products apart from using them as a well-known road construction materials. Hereby, we report the fabrication and applications of monolithic polymer-silica composites by ice-templating technique from laboratory waste silica-gels, using green approach. To the best of our knowledge, the fabrication of organic-inorganic hybrid sponges from the particles of hundreds of microns is not reported to date. Scaffolds S-60, S-120, S-180, and S-300, were prepared from laboratory discarded silica gels. The morphological, physicochemical, flame-retardant, and liquid absorbent properties of these self-standing scaffolds were analyzed. Results showed that the incorporation of silica particles in the scaffolds turned them into a flame-retardant sponge. These properties make the sponges ideal for making non-flammable cushions, applicable in automobiles, aircrafts, chemical laboratories, hospitals, and other areas of applications. Due to the large porous structures, these scaffolds possess excellent absorption properties and may absorb almost every kind of liquid ranging from oils to acids. Therefore, these scaffolds are also a remarkable absorber for oils and hazardous liquids spillage, such as acids, and can be used as foam for chemical packing applications. (C) 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acid absorber; Flame-retardant; Ice-templating; Laboratory silica waste; scaffolds